Plasmalogens in Innate Immune Cells: From Arachidonate Signaling to Ferroptosis - Jesús Balsinde; María A. Balboa (Biomolecules)
Polyunsaturated fatty acids such as arachidonic acid are indispensable components of innate immune signaling. Plasmalogens are glycerophospholipids with a vinyl ether bond in the sn-1 position of the glycerol backbone instead of the more common sn-1 ester bond present in “classical” glycerophospholipids. This kind of phospholipid is particularly rich in polyunsaturated fatty acids, especially arachidonic acid. In addition to or independently of the role of plasmalogens as major providers of free arachidonic acid for eicosanoid synthesis, plasmalogens also perform a varied number of functions. Membrane plasmalogen levels may determine parameters of the plasma membrane, such as fluidity and the formation of microdomains that are necessary for efficient signal transduction leading to optimal phagocytosis by macrophages. Also, plasmalogens may be instrumental for the execution of ferroptosis. This is a nonapoptotic form of cell death that is associated with oxidative stress. This review discusses recent data suggesting that, beyond their involvement in the cellular metabolism of arachidonic acid, the cells maintain stable pools of plasmalogens rich in polyunsaturated fatty acids for executing specific responses.